Anti-colonial Reflexivity in Social Work: Re‑personalizing the settler colonial past and present as settlers - Matsunaga, Jennifer (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2024)
Encouraging a new way for non-Indigenous researchers to think reflexively through their positionality and relationship with Indigenous peoples, lands, and claims for decolonization in their research, this paper introduces the concept of anti-colonial reflexivity. Anti-colonial reflexivity describes the slow process of looking into our genealogies, not simply to locate the names of ancestors in a family tree, but to attempt to critically understand the sociopolitical worlds in which they lived in order to trace our lineage in relation to settler colonization. As an intervention into reflexive practice, anti-colonial reflexivity seeks to re-personalize the settler colonial past and present, and to make reflexivity a practice that develops new self-understanding and accountability.